A correlation on ultrasonication with nanocrystalline cellulose characteristics. (15th October 2020) - Mohd Ishak, Nurul Atikah; Khalil, Ibrahim; Abdullah, Fatimah Zahara; Muhd Julkapli, Nurhidayatullaili
Graphical abstract: Highlights: Vibration amplitude of ultrasonication enhances the NCC thermal properties. No derivational reactions occurred during hydrolysis and ultrasonication. Ultrasonication treatment improves the NCC crystallinity and yield. Abstract: Catalytic ionic liquid hydrolysis of cellulosic material have been considered as a green and highly efficient dissolution process. However, application of a pre-treatment process, i.e; ultrasonication enhances the hydrolysis of cellulose in ionic liquid by providing mechanical force. In this paper, we describe the impact of both chemical and mechanical approaches to produce nanocrytalline cellulose (NCC) with anticipated particle size, and crystallinity with improved yields. The ultrasonication treatment was evaluated in terms of treatment time and vibration amplitude. It was found that the lowest ultrasonication time (5 min) produced the NCC of highest crystallinity (73 %), but the lowest yield (84 %). In contrary, the highest ultrasonication vibration amplitude at 90 % produced NCC with highest crystallinity value (67 %) as well as yields (90 %). It concludes that ultrasonic pre-treatment improves the hydrolysis process of cellulose in ionic liquid with increasing yield and crystallinity of NCC.